An augmented small-signal model of InP HBT with its analytical-based parameter extraction technique. (March 2022) - Cheng, Lin; Lu, Hongliang; Xia, Minjie; Cheng, Wei; Zhang, Yuming; Zhang, Yimen
Abstract: A rigorous and systematic analytical-based parameter extraction technique for the augmented small-signal equivalent-circuit model dedicated to III-V-based heterojunction bipolar transistors (HBTs) is presented. The proposed extraction method relies exclusively on S -parameters measured at low and high frequencies. The extraction algorithm is derived by peeling peripheral elements from the small-signal equivalent circuit with very few simplified approximations throughout the whole extraction process. All of the elements' parameters of the small-signal equivalent-circuit model considering the base-collector and base-emitter capacitances distributed effect are determined accurately through the developed extraction technique. Excellent agreement is obtained demonstrating the comparisons between the small-signal S -parameters measured and modeled results for 0.7 μm InGaAs/InP HBTs over a wide range of bias points within the frequency range of 0.1–40 GHz, which verifies the validity and the accuracy of this model and extraction technique.